Social Media Videos as Learning Tool for Figh Ibadat: Measuring University Students’ Understanding through Post-Class Feedback (Contrarius Series: Law & Social Justice, 2026)
This study explores the role of social media videos in enhancing the teaching and learning of complex religious concepts within the Fiqh Ibadat elective course at Universiti Malaysia Terengganu. The course attracts students from diverse academic disciplines and varying levels of religious knowledge, which often limits the effectiveness of traditional teaching approaches. To address this challenge, the study employed a descriptive quantitative method using post-class feedback from 58 students. Findings revealed that 96.6% of students were already engaging with Fiqh Ibadat content on social media platforms such as YouTube, TikTok, Facebook, and Instagram, indicating the existence of an informal learning ecosystem. After exposure to selected video content, 98.3% reported clearer understanding of complex topics, especially those related to daily practices, while 98.3% expressed stronger interest in Fiqh rulings. Additionally, 100% agreed that Fiqh studies became more relevant to real life through these resources. The results suggest that social media videos provide flexible, accessible, and practical support to classroom learning. Therefore, it is recommended that university lecturers integrate curated social media content as a complementary tool to traditional instruction for improved learning outcomes in Islamic education.